WASH FIT implementation in Rohingya camps in Cox's Bazar Bangladesh – results after 1 year - Ahammadul Kabir; Morshed Mohammad Shahnewaz; Hossain Mohammad Arif; Wassie Bizuneh Assefa; Bhuiyan Abu Toha Md Rezuanul Haque; Arabella Hayter; Egmond Evers (Journal of Water, Sanitation and Hygiene for Development, 2023)
Water, sanitation, and healthcare waste management are essential services in healthcare facilities to ensure the quality of care and minimize infection risk. World Health Organization (WHO) Cox Bazar's sub-office supported the implementation of the Water and Sanitation for Health Facility Improvement Tool in 21 purposively selected HCFs in Rohingya refugee settlements. A total of 16 WASH FIT indicators from three of the seven WASH FIT domains (five on water, five on sanitation, and six on healthcare waste management) were monitored for 1 year employing a mixed method approach. After 1 year 67% of indicators in all three domains met minimum WASH FIT standards, indicating a significant (p ≤ 0.01) contribution to improved quality of care compared to 29% at the start in August 2018. By domain, 81% of water indicators (vs. 67% at the start), 76 vs. 24% for sanitation, and 48 vs. 33% for healthcare waste management met standards. Key informant interviews and focus group discussions affirm improvement in all three domains, including quality of care, staff satisfaction, and awareness of occupational risks and mitigation measures. Challenges remain, including limited budget, lack of leadership and absence of formal programs for improving water supply infrastructure, sanitation and healthcare waste management. HIGHLIGHTS First successful implementation of WASH FIT in an emergency.; Summarized key findings of changes in water, sanitation, and healthcare waste management domains.; Challenges included inexperienced manpower, limitation of resources, absence of leadership, logistics, and high population density.; Government incorporated WASH FIT ‘Focal Person’ and ‘Facility Improvement Plan’ in the ‘Minimum Package of Essential Health Services’ at Cox's Bazar level.;